Regulations and Guidelines for Chemigation - Haimanote K. Bayabil; Kati W. Migliaccio; Jonathan H. Crane; Teresa Olczyk; Qingren Wang (EDIS, 2020)
Chemigation is a process where an irrigation system is used for transport and delivery of agrochemicals, generally fertilizers and pesticides, to a crop (Haman and Zazueta, 2017). Drip or micro-sprinkler irrigation systems are often used in chemigation. If the irrigation is properly plumed and chemigation properly implemented, chemigation can help growers reduce chemical usage and costs as it is applied using existing irrigation distribution infrastructure. However, the irrigation system must first be outfitted with properly designed injection and safety equipment. In addition, it is important that the irrigation system is built to allow the injection of chemicals or fertilizers at a known rate and that ensures application uniformity. Knowing the correct concentration of chemicals during chemigation is critical as some chemicals could potentially damage plants. Chemigation of chemicals/fertilizers at higher concentrations could also lead to leaching and contamination of freshwater bodies. The purpose of this document is to provide a brief overview of the regulations and some helpful tips for growers interested in chemigation.